If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -5)(a + 3) = 0 Reorder the terms: (-5 + a)(a + 3) = 0 Reorder the terms: (-5 + a)(3 + a) = 0 Multiply (-5 + a) * (3 + a) (-5(3 + a) + a(3 + a)) = 0 ((3 * -5 + a * -5) + a(3 + a)) = 0 ((-15 + -5a) + a(3 + a)) = 0 (-15 + -5a + (3 * a + a * a)) = 0 (-15 + -5a + (3a + a2)) = 0 Combine like terms: -5a + 3a = -2a (-15 + -2a + a2) = 0 Solving -15 + -2a + a2 = 0 Solving for variable 'a'. Factor a trinomial. (-3 + -1a)(5 + -1a) = 0Subproblem 1
Set the factor '(-3 + -1a)' equal to zero and attempt to solve: Simplifying -3 + -1a = 0 Solving -3 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1a = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1a = 0 + 3 -1a = 0 + 3 Combine like terms: 0 + 3 = 3 -1a = 3 Divide each side by '-1'. a = -3 Simplifying a = -3Subproblem 2
Set the factor '(5 + -1a)' equal to zero and attempt to solve: Simplifying 5 + -1a = 0 Solving 5 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1a = 0 + -5 -1a = 0 + -5 Combine like terms: 0 + -5 = -5 -1a = -5 Divide each side by '-1'. a = 5 Simplifying a = 5Solution
a = {-3, 5}
| 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 | | F(x)=-3x-8f(2) | | 5+4/x | | 3/x+2/5 | | 5/x-2/x | | 3/5(30x) | | 12(4x-8)=4(12x+9) | | 6+8n-4=9n+32-7n |